Aerosol optical properties - Peters, D; Grainger, R; Thomas, G (2010)
Traditionally the atmospheric physics department at the University of Oxford has applied optimal estimation techniques for the retrieval of atmospheric properties of gases; temperature, pressure and volume mixing ratio from satellite measurements. This paper describes the latest novel application of these techniques in deriving aerosol optical properties in laboratory experiments. Two examples are given; a spectral resolved technique allows an aerosol refractive index to be derived over a wide wavelength range and a method of deriving single particle refractive index and size from a novel aerosol instrument suitable for in situ aerosol monitoring.